2023
DOI: 10.3389/fnins.2023.1184051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transcutaneous vagus nerve stimulation on healthy cognitive and brain aging

Abstract: Evidence for clinically meaningful benefits of transcutaneous vagus nerve stimulation (VNS) has been rapidly accumulating over the past 15  years. This relatively novel non-invasive brain stimulation technique has been applied to a wide range of neuropsychiatric disorders including schizophrenia, obsessive compulsive disorder, panic disorder, post-traumatic stress disorder, bipolar disorder, and Alzheimer’s disease. More recently, non-invasive forms of VNS have allowed for investigations within healthy aging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Additionally, neurotransmitters like acetylcholine, serotonin, dopamine, brain-derived neurotrophic factor (BDNF), and gamma-aminobutyric acid (GABA), as con rmed in neurophysiological studies [38] , might contribute to atVNS's mechanism of action. It is possible that atVNS reduces neuroin ammation through the cholinergic anti-in ammatory pathway [39] , enhances blood ow to speci c brain regions, in uences peripheral hemodynamics [4] and modulates parasympathetic activity [40] . Furthermore, our previous study showed that two weeks of atVNS improved sleep scores, which could be linked to the activation of the ascending reticular activating system [41] known for its role in regulating the sleep-wake cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, neurotransmitters like acetylcholine, serotonin, dopamine, brain-derived neurotrophic factor (BDNF), and gamma-aminobutyric acid (GABA), as con rmed in neurophysiological studies [38] , might contribute to atVNS's mechanism of action. It is possible that atVNS reduces neuroin ammation through the cholinergic anti-in ammatory pathway [39] , enhances blood ow to speci c brain regions, in uences peripheral hemodynamics [4] and modulates parasympathetic activity [40] . Furthermore, our previous study showed that two weeks of atVNS improved sleep scores, which could be linked to the activation of the ascending reticular activating system [41] known for its role in regulating the sleep-wake cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This network is involved in sustained attention, novelty detection, problem-solving, working memory, and decision-making ( Vincent et al, 2008 ; Marek and Dosenbach, 2018 ; De Ridder et al, 2022 ). Considering the function of the fronto-parietal network, tVNS may have an effect on improving cognitive function and may serve as a treatment strategy for cognitive impairment ( Naparstek et al, 2023 ; Trifilio et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These fibers modulate functions in organs such as the heart, lungs, and gastrointestinal tract, regulating anti-inflammatory reflexes, secretion, and peristalsis in the gastrointestinal tract ( Bonaz et al, 2018 ). Anatomical studies have shown that the VN projects centrally to subcortical brain structures including the cerebellum, thalamus, and hippocampus ( Yakunina et al, 2018 ; Trifilio et al, 2023 ), exerting excitatory effects on these neurons ( Rutecki, 1990 ). The VN transmits signals through four nuclei in the CNS, namely the nucleus tractus solitarius (NTS), the spinal trigeminal nucleus, the solitary nucleus and the dorsomedial nucleus (DMN; Berthoud and Neuhuber, 2000 ).…”
Section: Introductionmentioning
confidence: 99%